A Review of Peter Isard's Globalization and the International Financial System: What's Wrong and What Can Be Done? - Eichengreen, Barry (Journal of Economic Literature, 2006)
Peter Isard's recent book (Globalization and the International Financial System: What's Wrong and What Can be Done?, Cambridge University Press, 2005) provides a thoughtful and balanced review of the scholarly literature on the past operation and potential reform of the international monetary and financial system. The author's approach, from which much can be learned, is to draw lessons from the history of exchange rates and capital flows and, especially, from the financial crises of the 1990s. But this retrospective focus is also revealing of what is new and different about our current international monetary and financial environment and in the ongoing debate surrounding the future of its steward, the International Monetary Fund.